Myc depletion induces a pluripotent dormant state mimicking diapause - Scognamiglio, Roberta; Cabezas-Wallscheid, Nina; Thier, Marc Christian; Altamura, Sandro; Reyes, Alejandro; Prendergast, Áine M.; Baumgärtner, Daniel; Carnevalli, Larissa S.; Atzberger, Ann; Haas, Simon; von Paleske, Lisa; Boroviak, Thorsten; et al. (Cell, 2016)
Mouse embryonic stem cells (ESCs) are maintained in a naive ground state of pluripotency in the presence of MEK and GSK3 inhibitors. Here, we show that ground-state ESCs express low Myc levels.
Gesehen am 27.05.2020